2mp+3np+2mr+3nr=

Simple and best practice solution for 2mp+3np+2mr+3nr= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2mp+3np+2mr+3nr= equation:


Simplifying
2mp + 3np + 2mr + 3nr = 0

Reorder the terms:
2mp + 2mr + 3np + 3nr = 0

Solving
2mp + 2mr + 3np + 3nr = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3np' to each side of the equation.
2mp + 2mr + 3np + -3np + 3nr = 0 + -3np

Combine like terms: 3np + -3np = 0
2mp + 2mr + 0 + 3nr = 0 + -3np
2mp + 2mr + 3nr = 0 + -3np
Remove the zero:
2mp + 2mr + 3nr = -3np

Add '-3nr' to each side of the equation.
2mp + 2mr + 3nr + -3nr = -3np + -3nr

Combine like terms: 3nr + -3nr = 0
2mp + 2mr + 0 = -3np + -3nr
2mp + 2mr = -3np + -3nr

Reorder the terms:
2mp + 2mr + 3np + 3nr = -3np + 3np + -3nr + 3nr

Combine like terms: -3np + 3np = 0
2mp + 2mr + 3np + 3nr = 0 + -3nr + 3nr
2mp + 2mr + 3np + 3nr = -3nr + 3nr

Combine like terms: -3nr + 3nr = 0
2mp + 2mr + 3np + 3nr = 0

The solution to this equation could not be determined.

See similar equations:

| 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 |

Equations solver categories